2021
DOI: 10.1186/s13068-021-01900-6
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle greenhouse gas emissions of ethanol produced via fermentation of sugars derived from shrub willow (Salix ssp.) hot water extraction in the Northeast United States

Abstract: Background The amount of carbon dioxide in the atmosphere has been on the rise for more than a century. Bioenergy crops are seen by the Intergovernmental Panel on Climate Change as an essential part of the solution to addressing climate change. To understand the potential impact of shrub willow (Salix spp.) crop in the northeast United States, effective and transparent life cycle assessment of these systems needs to occur. Results Here we show, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These new revenues could foster the creation of context-driven sustainable solutions aligned with local social, environmental and economic characteristics, using an integrated biorefinery approach [49][50][51][52][53][54]. Looking at an integrated value chain, ethanol production from willow represents a real opportunity for CO 2 reduction depending on the carboneutrality of the electricity grid [55]. Lower selling prices for biomass and new potential revenue streams could foster the development of other valorization streams, such as bioproducts or secondary metabolites for willow phytofiltration biomass to fit integrated biorefinery [11].…”
Section: Using Phytofiltration Incentives Can Create Lower Selling Pr...mentioning
confidence: 99%
“…These new revenues could foster the creation of context-driven sustainable solutions aligned with local social, environmental and economic characteristics, using an integrated biorefinery approach [49][50][51][52][53][54]. Looking at an integrated value chain, ethanol production from willow represents a real opportunity for CO 2 reduction depending on the carboneutrality of the electricity grid [55]. Lower selling prices for biomass and new potential revenue streams could foster the development of other valorization streams, such as bioproducts or secondary metabolites for willow phytofiltration biomass to fit integrated biorefinery [11].…”
Section: Using Phytofiltration Incentives Can Create Lower Selling Pr...mentioning
confidence: 99%
“…Ethylene can also be produced from biomass via ethanol dehydration. , Most of the ethanol produced in the United States is from corn grains, but a promising low carbon pathway for ethanol is from agricultural residues, such as corn stover, or dedicated energy crops, such as poplar wood. Ethanol produced from these materials is referred to as cellulosic ethanol, and it has been shown that this can be a carbon-neutral, or nearly carbon-neutral, fuel. , In 2019, 142.7 billion gallons of motor gasoline were consumed in the United States. According to the current regulation, the maximum percentage of ethanol in motor gasoline is 10%, reaching an ethanol “blend wall” of 14.3 billion gallons.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol produced from these materials is referred to as cellulosic ethanol, and it has been shown that this can be a carbon-neutral, or nearly carbon-neutral, fuel. 19,20 In 2019, 142.7 billion gallons of motor gasoline were consumed in the United States. According to the current regulation, the maximum percentage of ethanol in motor gasoline is 10%, reaching an ethanol "blend wall" of 14.3 billion gallons.…”
Section: Introductionmentioning
confidence: 99%
“…This can aid in better understanding of climate impacts of bioenergy as biomass systems capture and emit carbon at different points in time. Several LCA studies have assessed Salix cultivation for bioenergy utilization [17,32,33,[36][37][38][39][40]. However, studies looking at the magnitude of impact of differences between Salix varieties on the overall bioenergy system are rare.…”
Section: Introductionmentioning
confidence: 99%